ALUMINIUM PHOSPHIDE POISONING: A CASE REPORT - Hirani, Shela Akbar Ali; Rahman, Arshalooz (Journal of Ayub Medical College Abbottabad, 2010)
This paper reports the case of a family in which three children were presented at Emergency Room (ER) with poisoning after the use of a pesticide at home. Initially, the cases were managed as routine cases of organophosphorus poisoning; however, the death of two children made the health team members realise that the poison’s effects were delayed and devastating. Later, the compound was identified as Aluminium Phosphide (ALP), and the life of the last surviving child in the family was saved.